Inside Back Cover: Wiring Laccase on Covalently Modified Graphene: Carbon Nanotube Assemblies for the Direct Bio‐electrocatalytic Reduction of Oxygen (Chem. Eur. J. 8/2015). Issue 8 (16th February 2015) - Lalaoui, Noémie; Le Goff, Alan; Holzinger, Michael; Mermoux, Michel; Cosnier, Serge
<x xml:space="preserve">Abstract</x> Orientation of the enzyme Laccase enabling direct electron transfer with functionalized reduced graphene oxide in the presence of carbon nanotubes led to a high performance biocathode. The image represents anthraquinone‐ functionalized reduced graphene oxide sheets orienting and wiring Laccase enzymes. The electrons involved in the electrocatalytic reduction of oxygen to water are supplied by the surrounding carbon nanotube matrix and transferred via graphene to the enzyme. For more details, see the Communication by S. Cosnier and co‐workers on page 3198 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>